Existence of a Nonautonomous SIR Epidemic Model with Age Structure - Junyuan Yang; Xiaoyan Wang (Advances in Difference Equations, 2010)
A nonautonomous SIR epidemic model with age structure is studied. Using integro-differential equation and a fixed point theorem, we prove the existence and uniqueness of a positive solution to this model. We conclude our results and discuss some problems to this model in the future. We simulate our analyzed results.